2010
DOI: 10.1038/jhh.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure lowering effect of lactotripeptides assumed as functional foods: a meta-analysis of current available clinical trials

Abstract: The oral assumption of lactotripeptides Valine-ProlineProline (VPP) and Isoleucine-Proline-Proline (IPP) as nutraceuticals or functional foods is supposed to improve blood pressure (BP) control by angiotensinconverting enzyme-inhibition. However, data derived from clinical trials have reached conflicting conclusions. To perform a meta-analysis of placebo-controlled clinical trials evaluating the anti-hypertensive effect of lactotripeptides assumed as nutraceuticals or functional foods. Trials identified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 37 publications
3
105
0
Order By: Relevance
“…Other studies have investigated at the effect of different types of milk peptides in patients with hypertension. Some meta-analyses have shown a significant effect on resting BP as measured at one standard time point during the day (18,19,20). A metaanalysis of the data from 15 studies showed a small effect on SBP, but no effect on DBP, as mentioned previously (4).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have investigated at the effect of different types of milk peptides in patients with hypertension. Some meta-analyses have shown a significant effect on resting BP as measured at one standard time point during the day (18,19,20). A metaanalysis of the data from 15 studies showed a small effect on SBP, but no effect on DBP, as mentioned previously (4).…”
Section: Discussionmentioning
confidence: 87%
“…There was an imbalance in the literature as more RCT were conducted using mainly one type of casein-derived peptides, called lactotripeptides (LTP). We, therefore conducted an updated meta-analysis on the impact of LTP on BP (14) , which included all available and relevant RCT and detailed subgroup and regression analyses, which were somewhat limited in previous meta-analyses in this area (15)(16)(17)(18) . We found a small, but significant reduction in both SBP (−2·95 mmHg (95 % CI −4·17, −1·73; P < 0·001)) and DBP (−1·51 mmHg (95 % CI −2·21, −0·80; P < 0·001)) after 4 weeks of LTP supplementation in pre-and hypertensive populations.…”
Section: Long-term Studies On Blood Pressurementioning
confidence: 99%
“…12,14,23 In the present study, 24-h systolic and diastolic blood pressure decreased significantly only in the peptide group ( À 2.3 and À 1.8 mm Hg, respectively), but the difference between the groups was not statistically significant. As seen in the present and other trials (see meta-analyses [22][23][24] ), the effect of lactotripeptides varies individually from subject to subject, which may result in clinically significant mean reductions in blood pressure not reaching statistical significance in this number of study population.…”
Section: Discussionmentioning
confidence: 87%
“…23 Another meta-analysis by Pripp 22 included intervention studies on both lactotripeptides and other peptides derived from food, and found a significant effect on systolic blood pressure of À 5.1 mm Hg and diastolic blood pressure of À 2.4 mm Hg. A very recent metaanalysis by Cicero et al 24 on 18 placebo-controlled trials, with altogether almost 1700 subjects, showed as a pooled effect of peptide-containing products a reduction of À 3.7 mm Hg in systolic and À 2.0 mm Hg diastolic pressure. On the other hand, three recent intervention studies showed no significant decreases in blood pressure after ingestion of 4.6-14 mg per day of lactotripeptides for 4-8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation